Pengaruh E-Wom, Brand Image dan Influencer Terhadap Keputusan Pembelian pada Tokopedia - Bintang Gorafli Wibowo; Andriansyah Bachtillah Putra (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research aims to examine the influence of E-Wom, Brand Image and Influencers on Purchasing Decisions at the Tokopedia Marketplace in DKI Jakarta. The population in this research is consumers who use the Tokopedia marketplace in DKI Jakarta, totaling 205 people. The population in this research are consumers who use the Tokopedia marketplace in Jabodetabek. Data analysis techniques used in this research include outer model testing (Convergent Validity, Discriminate Validity, Composite Reability), inner model hypothesis testing (R square value, Goodness of Fit Model boostraping), Data was collected by distributing questionnaires to consumers and processed using a program Smart PLS 4.0. The results of this research show that E-Wom has a positive and significant effect on purchasing decisions. Brand Image has a positive and significant effect on Purchasing Decisions. Influencers have a positive and significant influence on purchasing decisions.